Who sets the agenda? Locating the formation of public opinion during the Rantau by-election - Mohamed, Shafizan; Syed Abdullah Idid, Syed Arabi (IIUM Press, International Islamic University Malaysia, 2019)
This paper investigates whether online news that are shared on Facebook set the agenda for its readers. In response to the importance of social networking sites as sources of information, news media organizations have set up Facebook channels in which they publish news stories or links to articles. This allows for a wider news reach as well as audience participation. When audience members read and subsequently comment on news articles on Facebook, it becomes possible to identify public opinions and sentiments on the issues being covered. To investigate whether user comments mirror the issues and sentiments presented in the news articles, the agenda-setting approach was applied. Content analysis was used to analyse audience comments on over 450 news articles from 4 major newspapers written during the Rantau by-election in Malaysia (April, 2019). The findings showed that while the newspapers and the readers do share some issue salience, the relationship does not typify a traditional agenda-setting dynamic. The news readers are not just the ones receiving the news and issues. Rather, they are also commenters who are influencing how others receive news and issues hence disrupting the conventional public opinion model.